Significance of Glucose Addition on Chitosan-Glycerophosphate Hydrogel Properties - Dian Susanthy; Purwantiningsih Sugita; Suminar Setiati Achmadi (Universitas Gadjah Mada, 2016)
Chitosan-glycerophosphate hydrogel can be used as dental scaffold due to its thermosensitivity, gelation performance at body temperature, suitable acidity for body condition, biocompatibility, and ability to provide good environment for cell proliferation and differentiation. Previous study showed that glucose addition to the chitosan solution before steam sterilization improved its hydrogel mechanical strength. However, the effectiveness of glucose addition was still doubted because glucose might undergo Maillard reaction in that particular condition. The aims of this study are to confirm whether the glucose addition can increase the hydrogel mechanical strength and gelation rate effectively and also to compare their performance to be dental scaffold. This research was performed through several steps, namely preparation of chitosan-glycerophosphate solution, addition of glucose, gelation time test, gel mechanical strength measurement, functional group analysis, and physical properties measurements (pH, viscosity, and pore size). The result showed that glucose addition did not improve the hydrogel mechanical strength and gelation rate, neither when it was added before nor after steam sterilization. Glucose addition before steam sterilization seemed to trigger Maillard reaction or browning effect, while glucose addition after steam sterilization increased the amount of free water molecules in the hydrogel. Chitosan and glycerophosphate interact physically, but interaction between chitosan and glucose seems to occur chemically and followed by the formation of free water molecules. Glucose addition decreases the solution viscosity and hydrogel pore size so the hydrogel performance as dental scaffold is lowered.